The International Jewish Youth Camp at Szarvas: History, impact and future - Pasajlic, Mina (Nordisk judaistik/Scandinavian Jewish Studies, 2020)
The JDC-Lauder International Jewish Youth Camp at Szarvas is perceived today as the single most important Jewish outreach and educational programme in Central and Eastern Europe; it is a key symbol for Eastern European Jewry. This paper emphasises the importance of the Szarvas camp, located some 170 km south-east of Budapest in Hungary, and its impact on the Jewish identity of the Central and Eastern European participants, and by extension on their families and communities. It focuses on the camp’s history and uniqueness, and includes a personal experience on the part of the author, who has participated in the camp and today works as its programme director. It also presents information collected from those who have experienced the impact of the camp on themselves.